Analisis Kendala dalam Pelaksanaan Program Rehabilitasi oleh BPBD Kabupaten Bengkalis Pasca Kebakaran Hutan dan Lahan - Azmarida, Fhadilla; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This study evaluates the constraints in implementing rehabilitation policies after forest and land fires (Karhutla) in Mandau District, Bengkalis Regency, in 2022-2024. Forest and land fires in this area often cause significant environmental and social impacts, requiring practical rehabilitation efforts. This research used a qualitative method with a descriptive approach and a purposive sampling technique to identify relevant informants. Data were collected through interviews, observations, and documentation, and then the validity of the data was checked using triangulation techniques. Data analysis was conducted through data reduction, data presentation, and inference. This study revealed three main obstacles in implementing the rehabilitation policy: limited budget, lack of cooperation or going royong, and lack of socialization in the community.